GLP-1 agonists in anaesthetic practice - a review of clinical data and recommendations - Natalia Pokrywka; Marcelina Polak; Dawid Suwała; Paulina Hetnar; Milena Fortuna; Sebastian Kiper; Sławomir Toczek; Magdalena Tomala; Katarzyna Jastrowicz-Chęć; Klaudia Koryszko (Journal of Education, Health and Sport, 2025)
Abstract